A influência do gênero e da infecção materna na resposta à Leishmania braziliensis em filhotes de hamster - Lima, Lia Fernandes Alves de (2008)
Immunoglobulins, soluble parasite circulating antigens, immune cells, citokines and other cell-related products can be transferred from infected mothers to their young, leading to suppression or stimulation of the immune response to a homologous antigen. Several studies demonstrated an increased susceptibility to leishmania infection in males, however, a relation between gender and susceptibility on the subgenus Viannia is rarely described. The influence of gender and maternal infection to the Leishmania braziliensis response in hamster offspring were evaluated. Thirty-nine hamster offspring of infected mothers and non-infected mothers from both genders, with 04 weeks-old, similar weights and infected with the Leishmania braziliensis strain MHOM/BR/94/H-3227 were analyzed. Studies on footpad lesion size, parasite load on footpad and draining lymph nodes, ELISA and histopathology were conducted. After analyzing the data, we concluded that the male offspring had higher susceptibility to infection by L. braziliensis, regardless if they were born from an infected mother or a non-infected mother, and had presented a more indolent pattern of response than the females. The maternal infection by L. braziliensis in hamsters did not influence the course of the disease in the infection rate of the offspring. The more intense inflammatory response in the offspring born from an infected mother can possibly be correlated to a greater induction of inflammatory molecules, cytokines and chemokines, although this has not been evaluated in this study.